Avanços na aplicação de câmaras de dessorção para remoção e recuperação dos gases metano e sulfeto de hidrogênio dissolvidos em efluente de reator UASB no tratamento de esgoto doméstico - Lucas Martins Machado (2018)
The use of UASB reactors has been gaining increasing prominence in the national scenario. However, anaerobic degradation, the products generated may become undesirable, such as formed gases that remain dissolved in the effluent. Such gases can find detachment routes to the atmosphere, being responsible for bad odors and emissions of greenhouse gases. One way to remove these gases is from turbulence generated in controlled environment, favoring the detachment and removal of the same. In this sense, the present research aims to improve the unit of removal of dissolved gases, denominated as Desorption Chamber (CD), in pilot scale, aiming also the recovery of the CH4. From the expansion of the desorption unit in relation to studies developed by other authors, which now has 0,35 meters in diameter and 1,2 meters of drop height, and the average operating flow of 20 L/s, he researched two operating conditions, unfilled (simplified CD) and filled-in. The simplified CD presented results similar to those found in previous research and even after expansion, it obtained removals of 56% in H2S and 61% in CH4. Then, with the filling of the CD on a demonstration scale, there was an increase in the removal of dissolved gaseous compounds, with efficiencies close to 88% for H2S and 82% for CH4. When the objective of removing dissolved gases was added to that of recovering dissolved methane, the study was carried out on a pilot scale CD, which has 0,12 meters in diameter and a useful drop height of 1,50 meters, of which 1,0 meters with filling material, to facilitate the transfer between air-liquid phases. The relationship between influent sewage flow and exhaust flow (rQ) was 0.06, thus concentrating the methane in the generated waste gas. The removal removal efficiencies found were on average 65% for H2S and 57% for CH4 while the concentration of methane in the tail gas was 17%.